3,5-Diiodo-L-Thyronine (T2) Administration Affects Visceral Adipose Tissue Inflammatory State in Rats Receiving Long-Lasting High-Fat Diet - Petito, Giuseppe; Cioffi, Federica; Silvestri, Elena; De Matteis, Rita; Lattanzi, Davide; de Lange, Pieter; Lombardi, Assunta; Moreno, Maria; Goglia, Fernando; Lanni, Antonia; Senese, Rosalba (Frontiers in Endocrinology, 2021)
3,5-diiodo-thyronine (T2), an endogenous metabolite of thyroid hormones, exerts beneficial metabolic effects. When administered to overweight rats receiving a high fat diet (HFD), it significantly reduces body fat accumulation, which is a risk factor for the development of an inflammatory state and of related metabolic diseases. In the present study, we focused our attention on T2 actions aimed at improving the adverse effects of long-lasting HFD such as the adipocyte inflammatory response. For this purpose, three groups of rats were used throughout: i) receiving a standard diet for 14 weeks; ii) receiving a HFD for 14 weeks, and iii) receiving a HFD for 14 weeks with a simultaneous daily injection of T2 for the last 4 weeks. The results showed that T2 administration ameliorated the expression profiles of pro- and anti-inflammatory cytokines, reduced macrophage infiltration in white adipose tissue, influenced their polarization and reduced lymphocytes recruitment. Moreover, T2 improved the expression of hypoxia markers, all altered in HFD rats, and reduced angiogenesis by decreasing the pro-angiogenic miR126 expression. Additionally, T2 reduced the oxidative damage of DNA, known to be associated to the inflammatory status. This study demonstrates that T2 is able to counteract some adverse effects caused by a long-lasting HFD and to produce beneficial effects on inflammation. Irisin and SIRT1 pathway may represent a mechanism underlying the above described effects.